2016
DOI: 10.1111/hepr.12703
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of serum Wisteria floribunda agglutinin‐positive Mac‐2‐binding protein in treatment‐naïve chronic hepatitis B

Abstract: The WFA -M2BP level can be a useful marker for assessing liver histological findings in patients with treatment-naïve CHB, although it has several limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 33 publications
5
60
0
Order By: Relevance
“…Thus, 21 studies ware included in the final analysis. Characteristics of these studies are shown in Table . All studies were published between January 2013 and September 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 21 studies ware included in the final analysis. Characteristics of these studies are shown in Table . All studies were published between January 2013 and September 2016.…”
Section: Resultsmentioning
confidence: 99%
“…[24] Liver fibrosis stages were graded as F0 to F4 by expert pathologists in our hospital. In the present study, we defined advanced fibrosis as F3 or more, and no patients had ascites as noted in imaging studies.…”
Section: Methodsmentioning
confidence: 99%
“…Detection of HBs antigen and HBe antigen and measurement of HBV-DNA level were performed using commercial kits as formerly described. [24] We measured WFA + -M2BP level using stored sera. The method for measurement of WFA + -M2BP level was as described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is well in line with recent reports from Japan. Ishii et al found that the median serum WFA+-M2BP level was 1.2 COI in treatment of naive chronic hepatitis B patients [28]. Ichikawa et al reported that serum WFA+-M2BP level was 0.97 COI in 112 treatment naive patients with HBV-related chronic hepatitis and liver cirrhosis [17].…”
Section: Discussionmentioning
confidence: 99%